2019
DOI: 10.22331/q-2019-07-09-161
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental limits on low-temperature quantum thermometry with finite resolution

Abstract: While the ability to measure low temperatures accurately in quantum systems is important in a wide range of experiments, the possibilities and the fundamental limits of quantum thermometry are not yet fully understood theoretically. Here we develop a general approach to low-temperature quantum thermometry, taking into account restrictions arising not only from the sample but also from the measurement process. We derive a fundamental bound on the minimal uncertainty for any temperature measurement that has a fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 49 publications
11
82
0
Order By: Relevance
“…Our results also demonstrate that thermometry with a vanishing absolute error at low temperature is possible with finite resolution, answering an interesting question left open by previous work [31,34,36]. For systems with a heat capacity that vanishes at low temperatures, a property often included in the third law of thermodynamics, the relative error must diverge, regardless of the available resolution [31]. The absolute error may either also diverge, stay constant, or vanish, with the latter thus being the best behavior one can hope for.…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…Our results also demonstrate that thermometry with a vanishing absolute error at low temperature is possible with finite resolution, answering an interesting question left open by previous work [31,34,36]. For systems with a heat capacity that vanishes at low temperatures, a property often included in the third law of thermodynamics, the relative error must diverge, regardless of the available resolution [31]. The absolute error may either also diverge, stay constant, or vanish, with the latter thus being the best behavior one can hope for.…”
Section: Introductionsupporting
confidence: 83%
“…This results in a measurement-independent quantity, the quantum Fisher information F Q T [40]. Within the canonical ensemble, it can be shown that a projective measurement of the system energy is optimal [31,37]. The quantum Fisher information is then related to the variance of the system energy…”
Section: A Quantifying the Estimation Precisionmentioning
confidence: 99%
See 3 more Smart Citations